Racial/Ethnic Differences in Pediatric Emergency Department Wait Times. Issue 2 (16th February 2022) - Johnson, Tiffani J.; Goyal, Monika K.; Lorch, Scott A.; Chamberlain, James M.; Bajaj, Lalit; Alessandrini, Evaline A.; Simmons, Timothy; Casper, T. Charles; Olsen, Cody S.; Grundmeier, Robert W.; Alpern, Elizabeth R.; ,
Abstract : Objectives: Wait time for emergency care is a quality measure that affects clinical outcomes and patient satisfaction. It is unknown if there is racial/ethnic variability in this quality measure in pediatric emergency departments (PEDs). We aim to determine whether racial/ethnic differences exist in wait times for children presenting to PEDs and examine between-site and within-site differences. Methods: We conducted a retrospective cohort study for PED encounters in 2016 using the Pediatric Emergency Care Applied Research Network Registry, an aggregated deidentified electronic health registry comprising 7 PEDs. Patient encounters were included among all patients 18 years or younger at the time of the ED visit. We evaluated differences in emergency department wait time (time from arrival to first medical evaluation) considering patient race/ethnicity as the exposure. Results: Of 448, 563 visits, median wait time was 35 minutes (interquartile range, 17–71 minutes). Compared with non-Hispanic White (NHW) children, non-Hispanic Black (NHB), Hispanic, and other race children waited 27%, 33%, and 12% longer, respectively. These differences were attenuated after adjusting for triage acuity level, mode of arrival, sex, age, insurance, time of day, and month [adjusted median wait time ratios (95% confidence intervals): 1.11 (1.10–1.12) for NHB, 1.12 (1.11–1.13) for Hispanic, and 1.05 (1.03–1.06) for other race children compared with NHW children]. Differences in wait time for NHB and other race children were no longer significant after adjusting for clinical site. Fully adjusted median wait times among Hispanic children were longer compared with NHW children [1.04 (1.03–1.05)]. Conclusions: In unadjusted analyses, non-White children experienced longer PED wait times than NHW children. After adjusting for illness severity, patient demographics, and overcrowding measures, wait times for NHB and other race children were largely determined by site of care. Hispanic children experienced longer within-site and between-site wait times compared with NHW children. Additional research is needed to understand structures and processes of care contributing to wait time differences between sites that disproportionately impact non-White patients.